An officer and a gentleman - Gere, Richard, 1949-; Winger, Debra, 1955-; Keith, David, 1954-; Loggia, Robert; Blount, Lisa.; Eilbacher, Lisa.; Gossett, Louis, Jr., 1936-; Hackford, Taylor, 1945-; Elfand, Martin; Nitzsche, Jack.; Stewart, Douglas Day.; Paramount Pictures Corporation; et al. (Hollywood, CA : Paramount, 2007)
A timeless tale of romance, friendship, and growth. Loner Zack Mayo enters Officer Candidate School to become a Navy pilot and in thirteen weeks he learns the importance of discipline, love and friendship.
Originally produced as a motion picture in 1982.
Special features: Commentary by director Taylor Hackford; An officer and a gentleman; 25 years later; Return to Port Townsend; True stories of military romance; The music of An officer and a gentleman; Gere and Gossett: hand-to-hand combat; photo gallery.
Music by Jack Nitzsche ; editor, Peter Zinner ; director of photography, Donald Thorin.
Richard Gere, Debra Winger, David Keith, Robert Loggia, Lisa Blount, Lisa Eilbacher, Louis Gossett, Jr.
MPAA rating: R ; CHV rating: 18A.
DVD; NTSC, Dolby Digital 5.1 surround, mono.
Keywords: United States. -- Navy -- Military life -- Drama; United States. -- Navy; Man-woman relationships -- Drama; Man-woman relationships; Armed Forces -- Military life; Feature films -- United States; Drama; Feature films; Feature films